Nothing happens here: Songs about Perth. (August 2016) - Stratton, Jon; Trainer, Adam
This essay examines Perth as portrayed through the lyrics of popular songs written by people who grew up in the city. These lyrics tend to reproduce the dominant myths about the city: that it is isolated, that it is self-satisfied, that little happens there. Perth became the focus of song lyrics during the late 1970s time of punk with titles such as 'Arsehole of the Universe' and 'Perth Is a Culture Shock'. Even the Eurogliders' 1984 hit, 'Heaven Must Be There', is based on a rejection of life in Perth. However, Perth was also home to Dave Warner, whose songs in the 1970s and early 1980s offered vignettes, which is itself a title of one of Warner's tracks, of the youthful, male suburban experience. The essay goes on to examine songs by the Triffids, Bob Evans, Sleepy Township and the Panda Band.